Building Capability in Construction Projects: a relationship-based approach - Davis, Peter; Walker, D. (Emerald Group Publishing, 2009)
Purpose: The aim of this paper is to propose a way that the development of human social relationship capital can be identified and measured in a construction project environment. Design/methodology/approach: Theory on the creation of social capital and consequent intellectual capital between parties to collaborative project procurement is explored. This is an exploratory study using grounded theory. Findings: A proposed capability maturity model (CMM) is posited that can be used to measure improvement in developing human social capital, and assisting in project strategy formulation. Two recent Australian alliance projects are analysed using the model to gain insights into how the quality of relationships within project alliances can be assessed. Practical implications: The model described in this paper may be used to measure performance or as an initial step towards strategising a change management plan based upon identifying a “current” situation. Originality/value: Each alliance is unique and so its goals with regard to social capital will vary. Accordingly the results should be viewed accordingly. Work in this area using a CMM approach is relatively rare, and so this paper provides a novel way of measuring a complex concept such as social capital.